A SEMANTIC BASED SEARCH FOR TEST CASE REPOSITORY - Shivakumar Swamy N, Sanjeev C. Lingareddy (International Journal of Research Science and Management, 2015)
Semantic Web [1] is a new generation web which emphasize on the effective utilization of Meta data as semantic/relevant information of a resource to derive its context. In semantic web the meta data is represented as RDF (Resource Description Framework) [2-3] and every object in RDF is conceptualized using the Ontology. The ontology describes the concepts and the relationship between the concepts. In this paper a new solution is proposed which uses the semantic information of test cases to search for efficient unit test, test case and test suite from the huge repository of test cases. The semantic information for every test case is represented using RDF describing the coverage information for every test case. The coverage analysis is considered as important criteria for ranking the unit test, test case and test suite. The search results can be filtered by with the explicit specification of coverage criteria.